Pharmacokinetics of Standard- and Reduced-Dose Recombinant Human Soluble Thrombomodulin in Patients with Septic Disseminated Intravascular Coagulation during Continuous Hemodiafiltration - Watanabe, Eizo; Yamazaki, Shingo; Setoguchi, Daisuke; Sadahiro, Tomohito; Tateishi, Yoshihisa; Suzuki, Tatsuya; Ishii, Itsuko; Oda, Shigeto (Frontiers in Medicine, 2017)
Introduction Recombinant human soluble thrombomodulin (rTM) is reportedly excreted by the kidneys; therefore, the recommended dose for patients with renal impairment is one-third of the standard dose. The aim of this study was to evaluate whether this reduced dose of rTM achieves effective drug concentrations that are comparable to those of the standard dose in treating sepsis-induced disseminated intravascular coagulation (DIC) during continuous hemodiafiltration (CHDF). Methods Eight patients in an intensive care unit were randomized to receive either reduced-dose (0.02 mg/kg, n = 4) or standard-dose (0.06 mg/kg, n = 4) rTM. We evaluated the effect of standard dose in comparison to that of reduced dose on the pharmacokinetics (PKs) of rTM for the sepsis-induced DIC patients receiving CHDF. Patients received rTM during a 30-min infusion for six consecutive days. PK parameters of rTM were analyzed using the one-compartment model. Results The elimination half-life, clearance (T1/2), and distribution volume of sTM were similar between the reduced and standard doses. The maximum concentration (Cmax) and area under the concentration–time curve (AUC) of sTM were approximately 2.5 times higher with standard-dose daily infusions than that with reduced-dose drip infusions (p = 0.041 and 0.062, respectively). The time when the blood concentration of sTM was >500 ng/mL, i.e., the holding time, was significantly longer with standard-dose infusions than those with reduced dose (p = 0.039). Conclusion rTM displayed dose-dependent PK behavior at clinically relevant doses. During CHDF, effective blood concentration of rTM was not achieved with the reduced dose, and rTM was found to not bioaccumulate. Therefore, this pilot study suggests that reducing the rTM dose is unnecessary, even in sepsis-induced DIC patients who require CHDF. However, we need to perform a definitive study to determine the dosage of rTM for the case.